INVESTIGATION OF THE CORRELATIONS BETWEEN QUANTITATIVE TRAITS WHICH DETERMINE YIELD IN THE VINE CULTIVAR BOLGAR AND THE HYBRID COMBINATION BOLGAR X RUSSALKA 1 - Venelin Roychev; Dushko Nedelkovski; Klime Beleski (Goce Delcev University of Štip, 2020)
The correlations between quantitative traits, which determine yield in the vine cultivar Bolgar and F1progeny of the hybrid combination Bolgar x Russalka 1 have been investigated through Path analysis. It has been found that there are no highly significant traits for the formation of yield from this cultivar, for which the correlation coefficients, direct and total indirect influences have positive values. Positive correlations have been reported between the two parent cultivars and F1 progeny for the traits: shoot and fruiting shoot fertility coefficient, cluster width, total number of shoots, fruiting shoots and clusters. All studied fertility coefficients in the cultivar Bolgar exert positive direct influences, determined by moderate correlations, on the seedlings from F1 progeny. The correlations of the other traits and the influence of separate parent cultivars have positive or negative values, which can be used in the selection of valuable elite forms.
Keywords: quantitative traits, yield; seeded and seedless vine cultivar; F1 progeny; correlations; direct and indirect influences; Path analysis